2015
DOI: 10.1037/a0038657
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts in a longitudinal sample of adolescents followed through adulthood: Evidence of escalation.

Abstract: Objectives This study was designed to examine escalation in repeat suicide attempts from adolescence through adulthood, as predicted by sensitization models (and reflected in increasing intent and lethality with repeat attempts, decreasing amount of time between attempts, and decreasing stress to trigger attempts) Method In a prospective study of 180 adolescents followed through adulthood after a psychiatric hospitalization, suicide attempts and antecedent life events were repeatedly assessed (M = 12.6 asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 80 publications
2
48
0
1
Order By: Relevance
“…Throughout the study, trained clinicians (M.D., Ph.D., or Master’s level) administered the Interview Schedule for Children and Adolescents (ISCA) or its version for Young Adults (YAIS), and associated diagnostic addenda, using either the intake version, or the follow up version, which covered the time since the last assessment (Sherrill and Kovacs, 2000). The inter-rater reliability of these symptom-based, semi-structured psychiatric interviews have been reported as satisfactory by us (Sherrill and Kovacs, 2000) and other investigators (Goldston et al, 2015). Using pre-coded, structured data sheets, interviewers also gathered psychosocial data, including information on treatment exposure.…”
Section: Methodsmentioning
confidence: 64%
“…Throughout the study, trained clinicians (M.D., Ph.D., or Master’s level) administered the Interview Schedule for Children and Adolescents (ISCA) or its version for Young Adults (YAIS), and associated diagnostic addenda, using either the intake version, or the follow up version, which covered the time since the last assessment (Sherrill and Kovacs, 2000). The inter-rater reliability of these symptom-based, semi-structured psychiatric interviews have been reported as satisfactory by us (Sherrill and Kovacs, 2000) and other investigators (Goldston et al, 2015). Using pre-coded, structured data sheets, interviewers also gathered psychosocial data, including information on treatment exposure.…”
Section: Methodsmentioning
confidence: 64%
“…An interrater reliability trial indicated high levels of agreement (96.4%; Îș = 0.92) in ratings of severity of STBs. 40 …”
Section: Methodsmentioning
confidence: 99%
“…Follow-up assessments were initially scheduled every six to eight months post-hospitalization but were later tapered to reduce participant burden and study costs until assessments were scheduled annually (please see 40 for additional details). The number of assessments and the timing between assessments varied within and between participants due to multiple factors, including participant preferences, lost contact, and lapses in grant funding.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Innamorati and colleagues (2008) found that suicide decedents had fewer SLEs during childhood and adolescence in comparison to those who attempted but did not die by suicide. Goldston et al (2015) also failed to find an association between precipitating stressors and future suicide attempts.…”
Section: Introductionmentioning
confidence: 96%